Impaired in vitro growth response of plasma-treated cardiomyocytes predicts poor outcome in patients with transthyretin amyloidosis - Hein, Selina; Furkel, Jennifer; Knoll, Maximilian; Siepen, Fabian aus dem; Schönland, Stefan; Hegenbart, Ute; Katus, Hugo; Kristen, Arnt; Konstandin, Mathias (Clinical research in cardiology, 2021)
Direct toxic effects of transthyretin amyloid in patient plasma upon cardiomyocytes are discussed. However, no data regarding the relevance of this putative effect for clinical outcome are available. In this monocentric prospective study, we analyzed cellular hypertrophy after phenylephrine stimulation in vitro in the presence of patient plasma and correlated the cellular growth response with phenotype and prognosis.